2005
DOI: 10.1111/j.1752-1688.2005.tb03793.x
|View full text |Cite
|
Sign up to set email alerts
|

Die-Off of Pathogenic E. Coli O157:h7 in Sewage Contaminated Waters

Abstract: E. coli O157:H7 is a pathogen that can be present in sewage contaminated waters. This organism poses a health risk for humans who come in contact with these waters via drinking, swimming, or shellfish consumption. A risk assessment model is needed to evaluate or quantify this risk. One possibility is the use of a computer model to simulate the fate and transport of E. coli O157:H7 downstream from a discharge point [e.g., a separate sanitary sewer overflow (SSO)]. However, this computer model would require inpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 19 publications
5
48
2
Order By: Relevance
“…S. enterica serovar Typhimurium/pDs was cultivable from swine manure-amended soils for 55 to 120 days at 10°C and 25°C but only for 25 to 55 days from beef manure-amended soils at these temperatures. Reported survival times of cultivable bacterial pathogens and FIB in field scale studies are similar to those reported in this work (12,39).…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…S. enterica serovar Typhimurium/pDs was cultivable from swine manure-amended soils for 55 to 120 days at 10°C and 25°C but only for 25 to 55 days from beef manure-amended soils at these temperatures. Reported survival times of cultivable bacterial pathogens and FIB in field scale studies are similar to those reported in this work (12,39).…”
Section: Resultssupporting
confidence: 76%
“…that antibiotic-resistant strains of S. enterica serovar Newport persisted for longer periods of time than their nonresistant counterparts in manure-amended soils. A fourth explanation may be that organisms enter a viable but not cultivable (VBNC) state, resulting in the appearance of an initial rapid decay, until stressed cells alter their physiology, followed by slower decay of more resilient organisms that remain cultivable, or as cells transition into and out of the VBNC state (8,12,14,27). Other potential sources of this behavior may include predation, biofilm formation, or the acquisition of genetic materials by a subpopulation of fecal bacteria from the native soil microbial community that favor their survival over counterparts that do not similarly adapt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the specifics of the facility permit and wastewater class, these exceedances may be acceptable in some cases. Studies have shown that FIB survival in surface waters varies from hours to days or even months if protected by sediments which make identifying the source of the FIB concentrations difficult [37,38]. The decay rate of FIB in surface water is a function of many ecological influences; therefore, water quality management, best management plan (BMP) development, watershed modeling, and risk assessment practices need to incorporate better methods as to how FIB interact with the environment, and furthermore, how well FIB accurately model true pathogenic concentrations in the watershed [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…First-order rate constants (k) were calculated for upper layer E. coli population declines for each , which is within the 0.00104 -3.40 d -1 range of literature inactivation rates for E. coli in freshwater systems (Crane and Moore, 1986;Flint, 1987;Davies and Evison, 1991;Easton et al, 2005). The huge range in inactivation rate reflects the diversity of environmental conditions studied.…”
Section: In-situ Inactivation Studiesmentioning
confidence: 99%